A survey to understand farmers' perceptions and risk factors for hoof diseases including footrot in sheep in New South Wales, Australia - Smith, Karen; Whittington, Richard J.; Green, Alexandra C.; Dhand, Navneet K.; Moses, Alicia; Grove, Annie; Thane, Tegan; Dhungyel, Om P. (Frontiers in Veterinary Science, 2022)
The aims of this study were to develop an understanding of farmers' perceptions and risk factors for footrot, including its less severe forms, and other hoof diseases in sheep in New South Wales (NSW). A questionnaire was developed and administered to sheep farmers in Local Land Services (LLS) regions across NSW. LLS staff selected sheep farmers who met the inclusion criteria which included farmers with a minimum of 100 sheep, a history of having had foot problems in their flock or having expressed an interest in improving sheep health and production. Farmers completed the questionnaire either by telephone or via the REDCap online survey platform. Descriptive analyses and multivariable logistic regression models were created. The survey was completed by 43 sheep farmers with a median farm size of 1,500 Ha and flock size of 2,300; footrot was present on 39% of farms while 75.6% had other hoof diseases. A flock of >3,000 sheep were more likely to have footrot than a smaller flock (OR = 11.99, 90% CI = 3.02–63.92, P-value = 0.005) and footrot was less likely to be present on farms when an Animal Health Statement was requested while purchasing sheep (OR = 0.10, 90% CI = 0.01–0.56, P-value = 0.04). Hoof conditions other than footrot were likely to be present in flocks when foot inspections were conducted at a time other than weekly inspections (OR = 0.13, 90% CI = 0.01–0.68, P-value = 0.04) and flocks kept on undulating ground were more likely to have diseases other than footrot compared to those kept on flat ground (OR = 3.72, 90% CI = 1.02–15.80, P-value = 0.09). Most farmers agreed that footrot including its less severe forms can cause production losses and negatively affect animal health and welfare. Limitations of the study were the sample size and dry environmental conditions prior to and during study period in many regions of NSW which limited the expression of footrot.